Color as a Cultural Resilience Strategy: Material-Semiotic Systems in Ghana's Indigenous Spirituality - Bawa, Al-Hassan; Salifu Cudjoe, Moses (UIN Sunan Gunung Djati Bandung, 2025)
Purpose: This study investigates how color operates as a material–semiotic system in Ghanaian indigenous spirituality and examines the ways in which this system contributes to cultural resilience across the Akan, Dagomba, and Ewe communities. The research seeks to understand how symbolic meanings and material practices of color mediate relationships between humans, ancestors, and spiritual forces, and how these systems adapt within contemporary contexts. Methodology:The study employs a qualitative ethnographic design conducted between January and June 2025 in three regions of Ghana. Data were collected through 18 semi-structured interviews, three focus group discussions, participatory observation of 15 ritual ceremonies, and analysis of 48 material artifacts. A reflexive thematic analysis using abductive reasoning was applied to identify patterns across symbolic meanings, material practices, and cross-cultural variations. Findings:Results reveal that the white–black–red triadic serves as a stable cosmological framework but is articulated differently through temporal orientations and ritual functions: white functions as terminal (Akan), initial (Dagomba), and continuous (Ewe); black demonstrates semantic complexity through affective, ritual-operational, and genealogical-structural expressions; and red shows varying valence from negative (Akan) to ambivalent (Dagomba) to positive (Ewe), requiring cultural mechanisms of regulation. Multicolored compositions further reveal a shared compositional grammar in which black acts as a structural integrator representing ancestral continuity. Implications: The study offers insights for cultural heritage preservation, ethical collaboration within creative industries, and the development of policy frameworks that support indigenous knowledge systems. It underscores the need for participatory approaches that recognize color not merely as aesthetic symbolism but as a living epistemic and cosmological resource sustaining community identity amid globalization and generational shifts. Originality and Value:This research advances a material–semiotic framework that bridges symbolic anthropology and material culture theory, introducing the concept of color as a strategy of cultural resilience. It demonstrates that color is not a passive representational code but an active performative agent that shapes spiritual, social, and cosmological relations. The study contributes novel cross-cultural evidence from West Africa and expands theoretical discussions on intangible cultural heritage, decolonial epistemology, and material agency.